PEMBENTUKAN PORTOFOLIO OPTIMAL MENGGUNAKAN MODEL INDEKS TUNGGAL INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE FEBRUARI 2021 – JANUARI 2022 - Rakhmi Ridhawati; Hanifah Hanifah; Siti Fatimah (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
This research aims to form an optimal portfolio of LQ 45 Index stocks using the Single Index Model for the period February 2021 - January 2022. The research method used is a qualitative method, and data collection is carried out with secondary data documentation obtained from the IDX website. The results of the study showed that only six stocks were optimal portfolio candidates from 43 sample candidates. This shows that the six stocks will provide greater returns than other stocks that are not included in the stock candidates.